The Effect Of Ginger Aromatherapy On Reducing Emesis Gravidarum In Pregnant Women In The First Trimester At The PMB Morina Neri Deli Serdang In 2025 - Sri Juliani; Mayang Wulan; Fina Kusuma Wardani; Dea Khairani Syahfitri (Jurnal Maternitas Kebidanan, 2026)
Emesis gravidarum is excessive nausea and vomiting that commonly occurs in pregnant women in the first trimester. This condition can disrupt daily activities, reduce nutritional intake, and impact the health of both the mother and the fetus. The use of non-pharmacological therapies such as ginger aromatherapy is considered safer and more effective because ginger contains active compounds like gingerol which have the ability to prevent or reduce nausea and vomiting in pregnancy.This study aims to determine the effect of ginger aromatherapy on reducing emesis gravidarum in pregnant women in the first trimester at PMB Morina Neri Deli Serdang in 2025. This type of research is quantitative with a pre-experimental design using a one-group pretest-posttest approach. The sample consisted of 20 respondents selected using purposive sampling technique. Data were collected through observation sheets using the PUQE Score (Pregnancy-Unique Quantification of Emesis) before and after the treatment of ginger aromatherapy for 5 consecutive days. The results of the study  showed that after conducting the Wilcoxon test with a P value of 0.000 < 0.05, it indicates that there is an effect of ginger aromatherapy tretment on reducing emesis gravidarum in pregnant women in the first trimester at PMB Morina Neri Deli Serdang in 2025. The conclusion of this study is that there is an effect of ginger aromatherapy on reducing emesis gravidarum in pregnant women in the first trimester at PMB Morina Neri Deli Serdang in 2025. It is expected that at PMB Morina Neri Deli Serdang, ginger aromatherapy can be utilized as a safe supportive therapy in midwifery services, particularly in handling complaints of nausea and vomiting in early pregnancy.